Extinction Coefficient and Production of Bushy Pepper at Several Radiation Levels - E. SURMAINI; R. HIDAYATI; . TRIWIDIATNO (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2000)
Extinction coefficient (k) described as plant capability to intercept solar radiation, furthermore determined energy conversion to dry matter. Pepper is C3 crop that have tolerance to shading. With knowing of optimal radiation level to growth and production can used to plan the cultivation and itsdevelopment. Research purposed to know extinction coefficient and optimal radiation level for production of bushy pepper. Experiment held on July-November 1997 on Research Installation of Research Institute of Spice and Medicinal Crop in Sukamulya, Sukabumi, West Java with 350 m above sea level and soil type is Alfisols. Research used spIit plot design with 3 replicates and 20 plants per plot. Main plot were radiation levels i.e 100, 75 and 50%. Sub plot were variety of bushy pepper i.e Petaling-1, Petaling-2 and Bengkayang. The highest k of three varieties was on 50% radiation level equals 243.2 cal/cm2/day that is 0.82 for Petaling-1, 0.78 for Petaling-2 and 0.89 for Bengkayang. When higher radiation received k value will be decrease. Bushy pepper that tolerance to low radiation, increasing k value able to increase plant production. The highest dried seed production of three varieties were on 50% radiation level, i.e 98.5 g/plant on Petaling-1, 82.6 g/plant on Petaling-2 and 91.6 g/plant on Bengkayang.